Similar Value Demonstrated in the Short-Term Outcomes of Superior Capsular Reconstruction and Reverse Shoulder Arthroplasty for Massive Rotator Cuff Tears - Andrew M. Gabig, M.D; Stephen S. Burkhart, M.D; Patrick J. Denard, M.D; J. Michael Proffitt, Ph.D; Robert U. Hartzler, M.D., M.S (Elsevier, 2023)
Purpose: The purposes of this study were to investigate the difference in value (benefit to cost ratio) of dermal allograft superior capsular reconstruction (SCR) versus reverse total shoulder arthroplasty (rTSA) for the treatment of massive rotator cuff tears (MRCTs) without arthritis; to compare the patient populations selected for the operations and report pre- and postoperative functional data; and to understand other characteristics of the 2 operations, including operating time, use of institutional resources, and complications. Methods: A retrospective, single-institution analysis during the study period 2014-2019 with MRCT treated with SCR or rTSA by 2 surgeons with complete institutional cost data and minimum 1-year clinical follow-up with American Shoulder and Elbow Surgeons (ASES) score. Value was defined as ΔASES/(total direct costs/$10,000). Results: Thirty patients underwent rTSA and 126 patients SCR during the study period with significant differences noted in patient demographics and tear characteristics between the groups (patients who underwent rTSA were older, less male, had more pseudoparalysis, had greater Hamada and Goutallier scores, and had more proximal humeral migration). Value was 25 and 29 (ΔASES/$10,000) for rTSA and SCR, respectively (P = .7). The total costs of rTSA and SCR were $16,337 and $12,763, respectively (P = .7). Both groups experienced substantial improvements in ASES scores: 42 for rTSA vs 37 for SCR (P = .6). The operative time for SCR was much longer (204 vs 108 minutes, P < .001) but complication rate lower (3% vs 13%, P = .02) versus rTSA. Conclusions: In a single institutional analysis of the treatment of MRCT without arthritis, rTSA and SCR demonstrated similar value; however, the value calculation is highly dependent on institution specific variables and duration of follow-up. The operating surgeons demonstrated different indications in selecting patients for each operation. rTSA had an advantage over SCR in shorter operative time, whereas SCR demonstrated a lower complication rate. Both SCR and rTSA are demonstrated to be effective treatments for MRCT at short-term follow-up. Level of Evidence: III, retrospective comparative study.